Hirnantian (Latest Ordovician) sponge spicules from the Precordillera at high latitudes of the Western Gondwana - Beresi, Matilde Sylvia (2022)
An assemblage of isolated and scarce sponge spicules was discovered on the bedding planes of fine sandstone lenses of the Don Braulio Formation (Hirnantian-Llandovery) at the Villicum Range, Eastern Precordillera of San Juan Province, Argentina. All spicules are from a short interval belonging to the Metabolograptus persculptus graptolite Zone (Hirnantian, Late Ordovician). The spicule assemblage exhibits low diversity and consists of dominant hexactins (six rays) including possible pentactins (five rays) and one stauractin (four rays). The Hirnantian spicules evidence the existence of communities of hexactinellid and probably reticulosan sponges of the shallow-sea floor community of the Precordillera platform at the western margin of Gondwana. They represent one of the few examples of sponges inhabiting cold-water in shallow siliciclastic environments at high palaeolatitudes of peri-Gondwana during the post-mass extinction transgression interval during the late Ordovician.